The Western Trypillia Culture House from the Settlement of Kamianets-Podilskyi, Tatarysky, 3950 — 3900 BCE - Diachenko, O.V.; Sobkowiak-Tabaka, I.; Levinzon, Ye.Yu. (Археологія і давня історія України, 2021)
This paper presents the results of excavations of the Western Trypillia culture house at the settlement of Kamianets-Podilskyi, Tatarysky. We discuss the house construction techniques, location of the interior details and house collapse. Analogies from other regions of the Western Trypillia culture made possible the conclusions on spread of the house construction techniques and traditions of interior location from the Middle Dniester region to the Southern Buh and Dnipro interfluve.